Experimental analysis of CCA threshold adjusting for vehicle EWM transmission in V-CPS. (2016) - Han, Qingwen; Zeng, Lingqiu; Yang, Le; Liu, Yuebo
Vehicular cyber-physical system (V-CPS) offers the potential to significantly improve the safety, comfort and entertainment to motorists. The topic of emergency warning messages (EWMs) transmission is still most import for V-CPS because of the thousands of lives taken by traffic accident. The EWM dissemination is expected to inform the related vehicles in time. This paper proposed a new EWM dissemination mechanism based on the clear channel assessment (CCAth ) threshold adjusting method to reduce the transmission delay by shorten the sensing time for idle channel. Experimental results obtained from the testbed - EyeNet - showed that the proposed mechanism employing an appropriate CCAth setting can shorten the transmission delay with 12 ms, and guarantee a relative high successful dissemination rate about 60%.